If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 0.06x = 40 Solving X + 0.06x = 40 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-0.06x' to each side of the equation. X + 0.06x + -0.06x = 40 + -0.06x Combine like terms: 0.06x + -0.06x = 0.00 X + 0.00 = 40 + -0.06x X = 40 + -0.06x Simplifying X = 40 + -0.06x
| y=-3(x-2)(x-7) | | 19a-18a+7=-13 | | -6(2+6x)=-120 | | 3x^9y^7+6x^7y^6+9x=0 | | -5(2m-4n)= | | 1/2(8h)=36 | | 6+6(2x-1)=12x | | 2/v=1/8 | | -17=-13-6(4b+20) | | (y-8)+24=3(y-6) | | 15t+6t-11t=150 | | 7x-12x+31x+15x=+12-8 | | (x+59)+(x+51)+84=180 | | -12v+16=4(-3v+4) | | m+5-4=18 | | 5x-2=(14/3) | | 3/4b15 | | 11x-48=5x+10 | | 8n=87 | | 14-5(4f-6)=-3-17-20f | | 24a-22=4a(1-6a) | | 16x^3-12x^2+20x-15= | | 7x+2=7y-10 | | z-2.3=5.1 | | 2/5t=30 | | X^2+15x-160= | | 14s+3s-7s=200 | | 99+90+90+(x^2)=360 | | 4x+3x-x=+2-32+5 | | 3/5x-10=11 | | 2(-8m-16)=-4(4m+8) | | -y+13=-42 |